Quantitative measurements of mixing intensity in shake-flasks and stirred tank reactors. Use of the Mixmeter, a mixing process analyzer - Gerson, D F. (Biochemical engineering journal, 2001)
A new mixing probe has been developed which measures the motions of the fluid during mixing as pressure fluctuations and converts the measurements into a mixing signal (MS). The MS is the root mean square (RMS) pressure fluctuation in the 1-64Hz range as determined by a sensitive pressure sensor and a digital signal processor specifically designed for the purpose. The MS is a measure of the actual mixing flow of the fluid rather than a measurement of the input motions or energies into the reactor system (e.g. RPM, torque or power). In other studies, the MS has been measured as a function of mixing speed in numerous sized reactors from 10 to 1000l, and provides consistent and reproducible measurements. The MS increases monotonically as a function of mixing speed, with a change of slope corresponding to the transition from laminar to turbulent mixing regimes. Maps of MS as a function of location in the reactor are useful in understanding stirred tank reactor design and performance. Quantitative measurements of mixing are especially useful during process development as a tool to increase the success of scale-up during the transition from process development to manufacturing. Measurements at a fixed location in a given reactor are useful in understanding changes in mixing that occur during the course of a given process, and are useful in manufacturing situations where validated documentation of lot-to-lot consistency of mixing is required (e.g. pharmaceutical manufacturing). In addition, the probe has been used to measure mixing in vessels with vibrational mixers with similar results. The probe has been successfully used in feedback loops to control either mixing speed or vibrational mixing amplitude in order to maintain constant mixing of the fluid during processing. With this system it is possible to maintain constant mixing over a wide range of fluid volumes in a given reactor, and, for instance, to compensate for changes in viscosity throughout the course of the process. Adaptations of this system for the measurement of mixing in shake-flasks is described in this paper